PERAN EKSTRAKURIKULER PASKIBRA UNTUK MENINGKATKAN KEDISIPLINAN SISWA DI SMPN 2 CADASARI KABUPATEN PANDEGLANG - Ade Millatus Sa’adiyyah; Dede Rohmat Hidayat (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
In accordance with the educational objectives described in the National Education System Act No. 20 of 2003, that education in Indonesia is not only intended to educating the life of the nation but also shape the character of students. To develop character and a good attitude for students an educational institution is needed. Educational institutions in Indonesia consist of formal, informal and non-formal education channels. Through extracurricular activities, it was expected to develop abilities and have discipline in students, as well as the potential and achievements of students. Extracurricular activities are expected to be able to meet the needs of students, to gain knowledge and experience that will someday be useful for students in daily life. The research was carried out at SMPN 2 Casasari with the object of the paskibra supervisor and female students. to achieve that above goals, the researcher uses a qualitative approach and presents a type of descriptive research, using data collection techniques through methods: 1) observation; 2) interviews; 3) documentation. The results of the study showed that (1) the role of the paskibra in SMPN 2 Cadasari was quite good, because there was a United Nations and there was discussion through character guidance activities so that it would improve discipline. (2) constraints faced by SMPN 2 Cadasari, paskibra there are clearly obstacles such as coming late, using attributes that are incomplete or different uniforms, late in attending extracurricular activities. (3) efforts to increase discipline in paskibra. Character guidance is conducted once a month, can shape the discipline of Paskibra members by giving advice, motivation and sharing experiences. More often participate in outside activities such as marching races.